SharePoint 2010 six-in-one - Geier, Chris C. (Programmer to programmer., 2011)
A team of SharePoint authorities addresses the six most essential areas of SharePoint 2010. SharePoint enables Web sites to host shared workspaces and is a leading solution for Enterprise Content Management. This book serves as one-stop shopping for concise coverage on six key areas that you need to know in order to get up and running with SharePoint 2010 quickly. After an introduction to the new features of SharePoint 2010, the author team of SharePoint experts walk you through branding and customization, workflow, business connectivity services, social networking and tools, the search functi.